Partial Least Square-Path Modeling Analysis of Factors Influencing the Consumptive Behaviour of Generation Z - Agustina, Melisa; Djakaria, Ismail; Abdussamad, Siti Nurmardia; Payu, Muhammad Rezky Friesta; Adityaningrum, Amanda (Jurusan Matematika FMIPA UNM, 2025)
Consumptive Behaviour refers to individuals’ purchasing behaviour without considering long-term needs and financial conditions. This research presents the results of an analysis of the consumptive behaviour of Generation Z in Dungingi Sub-District, Gorontalo City, selected because it represents the second-largest Generation Z population in the city. The study used the Partial Least Square-Path Modeling (PLS-PM) method to measure factors influencing consumptive behaviour: financial literacy, fear of missing out (FOMO), and hedonistic lifestyle. The sampling technique used was purposive sampling, resulting in 378 respondents aged 17-27 years who are employed. The analysis results indicate that financial literacy and FOMO significantly influence consumptive behaviour, with FOMO being the most dominant factor. The resulting model has a value of 0,930, meaning that the three latent variables can explain 93,0% of the consumptive behaviour of Generation Z. This study is expected to provide useful insights for policymakers and related parties in adressing consumptive behaviour issues among Generation Z. Keywords: PLS-PM; Consumptive Behaviour; Generation Z